2016
DOI: 10.1002/jcb.25636
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Laminin γ2 Expression by CDX2 in Colonic Epithelial Cells Is Impaired During Active Inflammation

Abstract: The expression of Caudal-related homeobox transcription factor 2 (CDX2) is impaired by tumor necrosis factor-α (TNF-α)-mediated activation of nuclear factor-κB (NF-κB) in ulcerative colitis (UC). Laminin subunit γ2 (LAMC2) is an epithelial basement membrane protein implicated in cell migration, proliferation, differentiation, as well as tumor invasion and intestinal inflammation, and its expression is enhanced by TNF-α in a NF-κB-dependent regulation of the recently identified LAMC2 enhancer. The aim was to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
(85 reference statements)
1
3
0
Order By: Relevance
“…However, we observed a strong induction of LAMB3 and LAMC2 in HUVECs after stimulation with the pro-in ammatory and pro-atherogenic cytokine, TNF-α. This is in line with previous data showing that TNF-α can regulate the expression of LAMC2 in epithelial cells [24,25].…”
Section: Discussionsupporting
confidence: 93%
“…However, we observed a strong induction of LAMB3 and LAMC2 in HUVECs after stimulation with the pro-in ammatory and pro-atherogenic cytokine, TNF-α. This is in line with previous data showing that TNF-α can regulate the expression of LAMC2 in epithelial cells [24,25].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, A . muciniphila can closely bind to laminin 18 , one of the important components of extracellular matrix which can regulate the migration, differentiation and anti-inflammatory responses of IECs 112 – 114 . A GWAS based study showed a strong connection between laminin β1 chain encoding gene and the susceptibility of UC 115 , and showed the laminin γ1 chain encoding gene as a susceptible locus of IBD 116 .…”
Section: A Muciniphila and Intestinal Homeostasis Of Hostmentioning
confidence: 99%
“…It has been well established that TLR4-mediated activation of NF-κB, a vital transcript factor involved in inflammation, is crucial in regulating intestinal inflammation. [27][28][29] Activation of the NF-κB signaling pathway in macrophages is associated with increased production of proinflammatory cytokines. 30 We have previously found that TLR4 is one of the important regulators of the NF-κB pathway in macrophages.…”
Section: Conflict Of Interestsmentioning
confidence: 99%